Comparison of Renal Function and Other Health Outcomes in Vegetarians versus Omnivores in Taiwan - Lin, Chih-Kuang; Lin, Deng-Juin; Yen, Chi-Hwa; Chen, Shiuan-Chih; Chen, Chun-Chieh; Wang, Tsun-Yen; Chou, Ming-Chih; Chang, Horng-Rong; Lee, Meng-Chih (Journal of Health, Population and Nutrition, 2010)
Renal disease is one of the top 10 leading causes of death, and the incidence of end-stage renal disease in Taiwan is the highest in the world. Many dietitians consider the diet of plant origin consumed by vegans to be 'lighter' and 'more healthful' than the diet of both plant and animal origin consumed by omnivores. Dietary protein has significant effects on renal functions. The study explored the effects of both the diets on renal functions. The study subjects included 102 Buddhist nun vegetarians and an equal number of matched control group (omnivores). A cross-sectional study was performed to investigate the effects of the diet of plant origin and the diet of both plant and animal origin on renal functions. There was no difference in the renal functions between the two groups. However, systolic blood pressure, blood urea nitrogen, serum sodium, glucose, cholesterol levels, and urinary specific gravity were lower in the vegetarian group. Although these results were compatible with general concepts regarding diet of plant origin, after adjusting for age, the duration of intake of this diet had no effect on the renal functions. Based on the findings, it is concluded that the renal functions, in terms of the estimated glomerular filtration rate, were not different between the vegetarians and the omnivores. Key words: Cross-sectional studies; Diet; Diet, Vegetarian; Renal function; Taiwan DOI: 10.3329/jhpn.v28i5.6155 J HEALTH POPUL NUTR 2010 Oct;28(5):470-475